Drivers and barriers in sustainable manufacturing implementation in Malaysian manufacturing firms - Nordin, Norani; Ashari, Hasbullah; Hassan, Mohamad Ghozali (2014)
Sustainable manufacturing practices seek to optimize production efficiency while minimizing environmental impact.Nowadays, the implementation of sustainable manufacturing practices in companies has increased.By implementing sustainable manufacturing practices, firms can gain better access to international markets; enhance business profile, consumer perceptions and corporate reputation and increase the manufacturing capacity.However, the implementation of sustainable manufacturing practices is posed to many drivers and barriers in light of the benefits manufacturing firms stand to gain from this initiative. This paper aims to investigate the drivers and barriers of sustainable manufacturing implementation in Malaysia. In this study, data were collected by using a self-administered questionnaires.The result shows that the increment in the overall cost of implementation is regarded as the main barrier to implementing sustainable manufacturing practices while environmental regulation and top management commitment are regarded as the main drivers.This research has been able to highlight the important barriers and drivers of implementing sustainable manufacturing practices through which industries can improve the manufacturing practices to offset the negativity on the environment.